Commitment, Forgiveness, and Relationship Self‐Regulation: An Actor Partner Interdependence Model of Relationship Virtues and Relationship Effort in Couple Relationships. (18th July 2017) - Novak, Joshua R.; Smith, Heather M.; Larson, Jeffry H.; Crane, D. Russell
Abstract : Dyadic data from 679 committed couples were used to examine associations between commitment, forgiveness, and perceptions of partner's relationship self‐regulation (RSR) behaviors—that is effort and strategies that partners exert to maintain the relationship. We found that for both partners, higher self‐reports of commitment and forgiveness were associated with higher perceptions of their partner's RSR. For females, higher commitment and forgiveness were associated with higher male perceptions of her RSR, and higher male forgiveness was associated with higher female perceptions of his RSR. These findings demonstrate the importance of marital virtues and relationship work and give credence to the marital competence model of "other‐centeredness" by Carroll et al. (2006, Journal of Family Issues, 27 (7), 1001). Clinical implications are discussed.